Stress, Visual and Musculoskeletal Complaints in Open Plan Office Staff - Vangelova K. (Sciendo, 2014)
The aim of the study was to identify the main ergonomic and organizational risks contributing to stress, visual and musculoskeletal disorders in open plan office workers. A total of 73 subjects of mean age 28.3 ±4.7 years were studied. Measurements of salivary cortisol and self-ratings for strain, fatigue, stress symptoms, visual and musculoskeletal complaints were performed. The work places were organized well, but the studied staff reported high work load and time pressure. The data showed higher cortisol levels during the workday under time pressure. High incidence of visual and musculoskeletal complaints mainly in the region of the back and the neck were found, associated with flickering and blinks on the screen monitors and overtime. Optimizing workplace organization could help reduce stress and health complaints of office staff.